2020
DOI: 10.1177/2470547020924844
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity and Polygenicity in Psychiatric Disorders: A Genome-Wide Perspective

Abstract: Genome-wide association studies (GWAS) have been performed for many psychiatric disorders and revealed a complex polygenic architecture linking mental and physical health phenotypes. Psychiatric diagnoses are often heterogeneous, and several layers of trait heterogeneity may contribute to detection of genetic risks per disorder or across multiple disorders. In this review, we discuss these heterogeneities and their consequences on the discovery of risk loci using large-scale genetic data. We primarily highligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 205 publications
(281 reference statements)
2
28
0
1
Order By: Relevance
“…In the last few decades, genome-wide association scans (GWAS) have been used to identify the genetic basis of chronic diseases, which revealed the influence of several common genetic variants on their risk. These conditions include but are not limited to cardiovascular disease (CVD) [ 13 , 14 ], cancer [ 15 ], and metabolic [ 16 ], neurodegenerative [ 17 ], and neuropsychiatric disorders [ 18 ]. However, despite the high heritability observed for these chronic diseases, the genetic variants identified explained a small proportion of the disease variability.…”
Section: Development and Perspectives For Italian Public Health Gementioning
confidence: 99%
“…In the last few decades, genome-wide association scans (GWAS) have been used to identify the genetic basis of chronic diseases, which revealed the influence of several common genetic variants on their risk. These conditions include but are not limited to cardiovascular disease (CVD) [ 13 , 14 ], cancer [ 15 ], and metabolic [ 16 ], neurodegenerative [ 17 ], and neuropsychiatric disorders [ 18 ]. However, despite the high heritability observed for these chronic diseases, the genetic variants identified explained a small proportion of the disease variability.…”
Section: Development and Perspectives For Italian Public Health Gementioning
confidence: 99%
“…Increasingly large genome-wide association studies (GWAS) show that brain disorders and related traits are driven by polygenic factors. Polygenicity has long been assumed for complex behavioural traits, but it is only now that we have come to fully appreciate the extreme form this polygenicity takes 1 . The brain is the logical organ of convergence for genetic effects on behavioural phenotypes, and quantitative neuroimaging can putatively trace some of these effects in living humans non-invasively 2 .…”
Section: Introductionmentioning
confidence: 99%
“…SCZ and BD are highly polygenic diseases, with many associated genetic variants with small effects, as demonstrated by several genome-wide association studies (GWAS) 14 17 . Moreover, several genetic-based studies have shown a limited contribution to support the diagnosis and/or the characterization of pathways underlying these major MDs, due to the well-recognized pleiotropic features and small size effect of each gene 18 , 19 . Therefore, none of genetic studies was adequate to reveal the mechanisms underlying the etiology and/or pathophysiology of SCZ and/or BD.…”
Section: Introductionmentioning
confidence: 99%